Biomimetic synthesis technology for preparation of Fe3O4-encapsulated biochar using in highly efficient peroxodisulfate activation - Wang, Yangyang; Xu, Jianfeng; Wang, Xiaoshu; Li, Tongtong; Zhang, Gen; Yan, Zheng; Liu, Jiancong; Wang, Lei (Frontiers in Chemistry, 2022)
The background value of iron in red soil is superior, primarily absorbed and homogeneously encapsulated in harvested biomass. However, this property on the high-value utilization of bionic iron-encapsulated biomass remains unknown. In this study, special biochar (Fe@BC) was obtained from this kind of biomass by one-step pyrolysis method, which was further used to activate peroxydisulfate (PDS) and degrade 2,4-dichlorophenol (2,4-DCP). The results showed that Fe3O4 was formed and homogeneously embedded in biochar at 500 oC. Comparing to catalysts prepared by impregnation pyrolysis (Fe/BC), Fe@BC exhibited excellent degradation performance (90.9%, k=0.0037 min-1) for 2,4-DCP. According to the free radicals quenching studies, hydroxyl radicals (·OH) and superoxide radicals (·O2-) were the dominant reactive oxygen species (ROS) in Fe@BC/PDS system. Importantly, a PDS adsorption model was established, and the electron transport and PDS activation in the core-shell structure were demonstrated by DFT calculations. Therefore, this study could supply a high-performance catalyst and significant implications for high-value biomass utilization in red soil.